Monitoring and Follow-up of the Effectiveness in the Latin American Pedagogical Management (Docentes 2.0 Journal, 2023)
Education has advanced in improvement, as well as in the development of the capacity to implement educational processes centered on the person; therefore, we are facing management in constant change according to the political, social, and economic environment. Therefore, the purpose of the present study was to describe the current state of the educational management of the educational director in its pedagogical dimension, as far as Latin America is concerned. This research was conducted under the systematic method, hermeneutic paradigm, with a qualitative approach of informative documentary-type narrative design, following the guidelines dictated in the PRISMA statement of systematic reviews. According to the selection criteria, 23 articles published between the years 2018 - 2022 were located. The results show how the vast majority of school principals dedicate very little time to their pedagogical practice support functions due to an excessive workload of purely administrative activities, which hinders the development and implementation of strategies to optimize the educational service and, therefore, the achievement of significant learning outcomes. In conclusion, good management seeks to re-evaluate public policies in education by analyzing the performance of management personnel in terms of changes to improve their effectiveness in their pedagogical dimension.
Keywords: Learning; teacher performance; principal; pedagogical management